'Vampires in the Canaries?' Miguel Aguerralde's Noctámbulo (2010): Revitalizing vampire traditions in the Hispanic periphery. Issue 2 (1st October 2019) - Davies, Rhian
This article is the first detailed study of Miguel Aguerralde's Canarian novel, Noctámbulo. It explores the way in which the author revitalizes vampire traditions, submerging his vampire protagonist, who is transformed into a paid assassin, into the seemingly incongruous environment of Gran Canaria. Challenging and subverting expectations, and offering readers the opportunity to regard its Canarian vampire protagonist as a Robin Hoodesque hero, Noctámbulo incites us to reflect profoundly on matters pertaining to the specific Canarian context (particularly the islands' status as 'the outcast' in relation to mainland Spain, issues concerning memory and grappling with the past), as well as on broader concerns. The article concludes by postulating that Noctámbulo is a liberating transnational novel, one which transcends genres and borders, refutes preconceived ideas and offers readers worldwide the opportunity to determine how they will interpret the work and envision their futures.